TO THE QUESTION OF URBAN DEVELOPMENT OF THE CENTRAL RAILWAY STATION COMPLEX ENSEMBLE IN KHARKIV CITY - Сергеева, Камила; Древаль, Ирина (Modern engineering and innovative technologies, 2017)
The features and meanings of important city-building ensembles - railway station complexes are considered in this work. Their evolutionary changes under the influence of a number of factors are regarded on the example of Kharkiv city. It is shown how the